Microbial Efflux Pump Inhibitors: A Journey around Quinoline and Indole Derivatives - Giada Cernicchi (MDPI AG, 2021)
Antimicrobial resistance (AMR) is a complex threat to human health and, to date, it represents a hot topic in drug discovery. The use of non-antibiotic molecules to block resistance mechanisms is a powerful alternative to the identification of new antibiotics. Bacterial efflux pumps exert the early step of AMR development, allowing the bacteria to grow in presence of sub-inhibitory drug concentration and develop more specific resistance mechanisms. Thus, efflux pump inhibitors (EPIs) offer a great opportunity to fight AMR, potentially restoring antibiotic activity. Based on our experience in designing and synthesizing novel EPIs, herein, we retrieved information around quinoline and indole derivatives reported in literature on this topic. Thus, our aim was to collect all data around these promising classes of EPIs in order to delineate a comprehensive structure–activity relationship (SAR) around each core for different microbes. With this review article, we aim to help future research in the field in the discovery of new microbial EPIs with improved activity and a better safety profile.